Design, analysis of the Genesio-Tesi chaotic system and its electronic experimental implementation - Mustafa, Mamat; Aceng, Sambas; Sundarapandian, Vaidyanathan (International Sciences Press, 2016)
In this paper, a Genesio-Tesi chaotic system with one quadratic term has been proposed, and its qualitative properties have been detailed. The dynamic behavior of the Genesio-Tesi chaotic attractor is analyzed. Specially, the Lyapunov spectrum and eigenvalue structure are calculated and the bifurcation diagram is sketched. Chaotic electronic implementation of Genesio-Tesi attractor were designed and simulated in MultiSIM. The system was implemented as an electronic circuit whose behavior confirms the numerical predictions.